2022
DOI: 10.1038/s41380-022-01801-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, environmental, and genetic risk factors for substance use disorders: characterizing combined effects across multiple cohorts

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Problems related to behavioral disinhibition, commonly referred to as externalizing, can have far reaching health consequences. We and others have shown that risk for EXT disorders overlaps with a variety of key public health outcomes at both the genetic and phenotypic level 11,[13][14][15][16][17][18]48 . In the current analysis, we leveraged these recent, novel insights into the underlying biology of EXT, extended analyses to multiple ancestries, and evaluated their correlates and consequences in the largest integrated healthcare system in the US.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Problems related to behavioral disinhibition, commonly referred to as externalizing, can have far reaching health consequences. We and others have shown that risk for EXT disorders overlaps with a variety of key public health outcomes at both the genetic and phenotypic level 11,[13][14][15][16][17][18]48 . In the current analysis, we leveraged these recent, novel insights into the underlying biology of EXT, extended analyses to multiple ancestries, and evaluated their correlates and consequences in the largest integrated healthcare system in the US.…”
Section: Discussionmentioning
confidence: 95%
“…Additional work is needed to ensure that the study results generalize beyond the VA. Third, we did not examine PGS in conjunction with social and environmental factors. Both polygenic and environmental risk factors are important for understanding key outcomes in veterans' health, including substance use disorders 48 , major depressive disorder 52 , and other mental health problems 53 . Many veterans are at risk for adverse environmental experiences due to poverty, minority status, and physical and psychiatric challenges 54 .…”
Section: Discussionmentioning
confidence: 99%
“…As our gene identification efforts continue to evolve, COGA has initiated efforts to combine genetic information with known environmental risk factors to predict risk for substance use disorders in clinical and population-based samples. 134,135 Although these are not yet ready for integration into clinical practice, we have begun to lay the groundwork for the utilization of genetic risk information by reviewing the current status of genetic feedback for psychiatric conditions, 136 studying public interest in receiving personalized genetic risk scores, 137 and examining how we can return complex risk information in ways that will promote healthy behavior. 138 It will be critical to carefully consider the benefits and potential harm that could result from the incorporation of genetic risk information into clinical care.…”
Section: Risk Prediction and Contributions To Precision Medicinementioning
confidence: 99%
“…The identification of these multiple variants will help predict the onset and development of individual risk for dependence. PGS analysis has been used to evaluate risk for AUD both by others 16,75,76 and within COGA [77][78][79][80][81][82]…”
Section: Combined Effect Of Multiple Aud-related Genetic Variants On ...mentioning
confidence: 99%